Fucoxanthin prevents breast cancer metastasis by interrupting circulating tumor cells adhesion and transendothelial migration - Wang, Weiyu; Fu, Chengbin; Lin, Mengting; Lu, Yusheng; Lian, Shu; Xie, Xiaodong; Zhou, Guiyu; Li, Wulin; Zhang, Yiping; Jia, Lee; Zhong, Chunlian; Huang, Mingqing (Frontiers in Pharmacology, 2022)
Metastasis is the leading cause of cancer-related death and a critical challenge in improving cancer treatment today. Circulating tumor cells (CTCs) adhesion to and across the vascular endothelium are critical steps in the establishment of micrometastatic foci away from the primary tumor. Therefore, we believe that interrupting CTCs adhesion to endothelium and transendothelial migration may efficiently prevent cancer metastasis. Fucoxanthin (Fx) is an algal carotenoid widely distributed in brown algae, macroalgae, and diatoms. Previous studies have found that Fx has various pharmacological activities, including antidiabetic, antioxidant, anti-inflammatory, anti-obesity, antimalarial, anticancer, and so on. However, it remains unclear whether Fx has a preventive effect on cancer metastasis. Here, we found that Fx interrupts breast cancer cells MCF-7 adhesion to endothelium and transendothelial migration, thus inhibiting CTCs-based pulmonary metastasis in vivo. The hetero-adhesion assay showed that Fx significantly inhibited the expression of inflammatory factor-induced cell adhesion molecules (CAMs) and the resulting adhesion between MCF-7 cells and endothelial cells. The wound-healing and transwell assays showed that Fx significantly inhibited the motility, invasion, and transendothelial migration abilities of MCF-7 cells. However, the same concentration of Fx did not significantly alter the cell viability, cell cycle, apoptosis, and ROS of breast cancer cells, thus excluding the possibility that Fx inhibits MCF-7 cell adhesion and transendothelial migration through cytotoxicity. Mechanistically, Fx inhibits the expression of CAMs on endothelial cells by inhibiting the NF-кB signaling pathway by down-regulating the phosphorylation level of IKK-α/β, IкB-α, and NF-кB p65. Fx inhibits transendothelial migration of MCF-7 cells by inhibiting Epithelial-to-mesenchymal transition (EMT), PI3K/AKT, and FAK/Paxillin signaling pathways. Moreover, we demonstrated that Fx significantly inhibits the formation of lung micrometastatic foci in immunocompetent syngeneic mouse breast cancer metastasis models. We also showed that Fx enhances antitumor immune responses by substantially increasing the subsets of cytotoxic T lymphocytes in the peripheral immune system. This new finding provides a basis for the application of Fx in cancer metastatic chemoprevention and suggests that interruption of the CTCs adhesion to endothelium and transendothelial migration may serve as a new avenue for cancer metastatic chemoprevention.